2016
DOI: 10.1080/09168451.2015.1135045
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 21 induction by activating transcription factor 4 is regulated through three amino acid response elements in its promoter region

Abstract: Fibroblast growth factor 21 (FGF21) is an endocrine growth factor, a regulator of fatty acids and glucose metabolism. Recently, it has been reported that FGF21 expression is regulated by activating transcription factor 4 (ATF4), a transcription factor activated by various stimuli such as endoplasmic reticulum (ER) stress. ATF4 binds to the amino acid response element (AARE), a binding site for ATF4, in the promoter region of the target genes. The two response elements for ATF4 (AARE1 and AARE2) have been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…This loop bypasses the negative feedback of glucocorticoids in the hypothalamic-pituitary-adrenal axis in order to sustain gluconeogenesis in liver during starvation [54]. Recently, it has been reported that FGF21 expression is regulated by activating transcription factor 4 (ATF4), a transcription factor activated by various stimuli such as endoplasmic reticulum (ER) stress [55]. ATF4 binds to the amino acid response element (AARE), a binding site for ATF4, in the promoter region of the target genes.…”
Section: Interventions That Modulates Fgf21 Synthesis and Secretionmentioning
confidence: 99%
See 2 more Smart Citations
“…This loop bypasses the negative feedback of glucocorticoids in the hypothalamic-pituitary-adrenal axis in order to sustain gluconeogenesis in liver during starvation [54]. Recently, it has been reported that FGF21 expression is regulated by activating transcription factor 4 (ATF4), a transcription factor activated by various stimuli such as endoplasmic reticulum (ER) stress [55]. ATF4 binds to the amino acid response element (AARE), a binding site for ATF4, in the promoter region of the target genes.…”
Section: Interventions That Modulates Fgf21 Synthesis and Secretionmentioning
confidence: 99%
“…ATF4 binds to the amino acid response element (AARE), a binding site for ATF4, in the promoter region of the target genes. The two response elements for ATF4 (AARE1 and AARE2) have been reported in the promoter region of FGF21 gene [55].…”
Section: Interventions That Modulates Fgf21 Synthesis and Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that FGF21 gene expression is directly regulated by ATF4 (7,8,12,22) and potentially XBP-1 (9). A previous study reported that FGF21 repressed ER stress by inhibiting phosphorylation of eIF2a, an upstream activating factor of ATF4 (9).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies revealed that expression of FGF21 is induced in response to ER stress and amino acid deprivation via activation of ATF4 (6)(7)(8)(9)(10)(11). The promoter region of FGF21 contains three response elements for ATF4, suggesting FGF21 is a direct target of ATF4 (12).…”
mentioning
confidence: 99%